The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1108/imds-05-2014-0132
|View full text |Cite
|
Sign up to set email alerts
|

Brand relationship, consumption values and branded app adoption

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 28 publications
5
92
0
Order By: Relevance
“…Bellman et al, 2011). Moreover, Peng et al (2014) remark that it is widely accepted that apps satisfy the utilitarian and nonutilitarian needs of consumers, and that this facilitates the consumers' decision to use a branded app. The usage itself exposes the consumer to several favourable features, which can bolster the feelings and attachment between the consumer and the brand, exerting positive effects such as sense of belongingness and sameness with the brand.…”
Section: Intention To Use Branded Appsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bellman et al, 2011). Moreover, Peng et al (2014) remark that it is widely accepted that apps satisfy the utilitarian and nonutilitarian needs of consumers, and that this facilitates the consumers' decision to use a branded app. The usage itself exposes the consumer to several favourable features, which can bolster the feelings and attachment between the consumer and the brand, exerting positive effects such as sense of belongingness and sameness with the brand.…”
Section: Intention To Use Branded Appsmentioning
confidence: 99%
“…Above all, branded apps can deliver important outcomes that can yield economic returns -e.g., in the form of positive attitudes, purchase intentions, advertising response and consumer engagement (Seitz and Aldebasi, 2016;Yang, 2016). Furthermore, branded apps represent tools that firms can use to establish new connections with customers and to reinforce existing ones, creating unique customer experiences (Kim, Lin and Sung, 2013;Peng, Chen and Wen, 2014). Moreover, branded apps differ to some extent from other mobile technologies, given the considerable potential for consumer engagement and interconnectivity (e.g., Seitz and Aldebasi, 2016;Yu, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consumption values theory has been used in many studies in marketing literature (see. Finch, 2006;Lin, Huang & Wang, 2010;Lin & Huang, 2012;Punj, 2011;Peng, Chen & Wen, 2014;Wang, Liao & Yang, 2013;Bolker, Gimpel & Hedman, 2009). Bolker et al (2009 had examined the experiences of smart phone users with the consumption values theory, and had concluded that all five consumption values have significant contributions to explain and understand the consumer experiences.…”
Section: Consumption Values Relevant To Mobile Banking Servicesmentioning
confidence: 99%
“…Following the technology acceptance model and its successors current empirical research applies the theoretical terms "perceived ease of use", "perceived usefulness" and "perceived risks" as central components to explain mobile app use in general (e.g. Kappor, Dwivedi, & Williams, 2014;Khalifa & Shen, 2008;Peng, Chen, & Wen, 2014;Schierz, Schilke, & Wirtz, 2010;Taylor & Levin, 2014;Yang, 2013;Yang, Lu, Gupta, & Cao, 2012). However, recent research begins to extend the model and to include more variables with respect to concrete application contexts of mobile apps-like brand marketing (Peng et al, 2014), mobile commerce (Khalifa & Shen, 2008) and mobile payment (Kappor et al, 2014;Schierz et al, 2010;Yang et al, 2012).…”
Section: Theory and Hypothesesmentioning
confidence: 99%